Formulation of fat substitute using plant-based fats simulating the properties of lard - Abdul Manaf, Yanty Noorzianna (2015)
Lard (LD) is a solid fat used as shortening in the manufacture of bread, cakes, cookies and other products due to its flavor and physical properties. However, the limitation of lard applications were concerned as the Muslims, Jews and vegetarians are not permissible to consume both pork and lard in any products. In addition, consumption of lard and other animal fats is not recommended since there is a growing negative perception about the implication of animal fats on human health. Therefore, lard alternative products are highly demanded from many Muslim majority countries to regularize food formulation according to the syariah compliance. If an alternative halal product is made available, it may serve as an import substitute as well as to satisfy the demand for alternative halal products. However, past studies on lard alternative fat substitute is very limited. Hence, a study was carried out to formulate lard alternative fat substitute by mixing various plant fats such as mee fat [Madhuca longifolia (MF)], palm stearin (PS), avocado fat (Avo), cocoa butter (CB), palm oil (PO) and soybean oil (SBO). At first, the binary (MF:PS), ternary (Avo:PS:CB) and quaternary (PO:PS:SBO:CB) (w/w) mixtures were formulated using the above mentioned fats at different ratios and their physico-chemical properties were compared to that of LD such as slip melting point (SMP), iodine value (IV), fatty acid (FA) composition using GC, triacylglycerol (TAG) composition using HPLC, thermal behavior using DSC and solid fat content (SFC) NMR. None of the plant based mixtures had a SMP and IV that were similar to that of lard. Even though there were diversity in fatty acids and triacylglycerol molecules, however, some of plant based mixtures showed similarity with some fatty acids and triacylglycerol molecules of LD. Binary (MF:PS) mixtures had higher saturated fatty acids (44.25-45.77%) and UStSt triacylglycerol contents (38.21-44.76%) compared to that of lard (37.38 and 26.60%, respectively). Meanwhile, the saturated fatty acid and UStSt triacylglycerol contents of ternary (Avo:PS:CB) (36.65-38.01% and 24.89-33.61%, respectively) and quaternary (PO:PS:SBO:CB) (34.44-36.79% and 22.47-24.86%, respectively) mixtures were almost similar to lard (37.38 and 26.60%, respectively). The cooling and heating profiles of plant based mixtures were differed from lard. However, the major melting peak of MF:PS (99:1), Avo:PS:CB (84:7:9) and all quaternary mixtures was found to be closest to that of lard at -3.59 °C. SFC profile compatibility of mixture was used as the main criteria to choose the best mixture under each set (binary, ternary and quaternary) as compared to that of lard. According to this, the SFC of binary mixture of MF:PS (99:1), ternary mixture of Avo:PS:CB (84:7:9) and quaternary mixture of PO:PS:SBO:CB (38:5:52:5) were almost similar and the least difference to that of lard. In the next stage, these selected plant based mixtures and lard were subjected to shortening production. The formulated shortenings were compared to that of lard shortening in term of their hardness using a texture analyzer (TA), consistency using a cone penetrator, polymorphism using XRD and microstructure behavior using PLM. The hardness (26.19-28.35 g) and adhesiveness (82.46-137 g/s) of formulated plant based shortening were not significantly different (p>0.05) compared to that of lard shortening (26.67 g and 123.88 g/s, respectively). The formulated plant based shortenings and lard shortening were categorized as plastic fats based on their consistency value (319.20-326.26 g/cm2) and displayed a mixture of β’ and β-form polymorphs of which the β’-form was found to be predominant. However, the polymorphism characteristic was not affected by crystallization behavior where the number and size of crystals in the formulated plant based shortenings were dissimilar to those of lard shortening. In the final stage, the functional properties of formulated plant based shortenings and lard shortening were compared in the production of cookie dough and cookie. The dough made with formulated plant based shortenings and LD shortening had a better consistency with increase of mixing time. However, dough made with binary (337 BU) and quaternary (300 BU) mixture shortenings had a closer consistency value at 15 min of the mixing time and there were also no significant differences (p>0.05) with dough made with LD shortening (333 BU). The dough made with formulated plant based shortenings and lard shortening had a maximum cookie spread at 3 min while baking in the oven. In the meantime, there was no significant difference (p>0.05) in elasticity of dough made with binary mixture shortening (65 BU) with dough made with LD shortening (63 BU). However, there were no significant differences (p>0.05) among cookies of different types of shortenings with regard to cookie hardness (1008.12-1015.75 g), diameter (72.33-72.95 mm), thickness (9.32-9.52 mm) and cookie spread ratio (7.65-7.8 mm). With regard to color, ANOVA results showed that there were no significant differences (p>0.05) in L, a, and b values of cookies made with binary (70.43, 8.12 and 19.55, respectively) and quaternary (69.23, 7.27 and 20.96, respectively) mixture shortenings and lard shortening (69.27. 7.03 and 18.79, respectively).